2003
DOI: 10.1128/jvi.77.8.4848-4857.2003
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Cattle with a Bovine Herpesvirus 1 Strain That Contains a Mutation in the Latency-Related Gene Leads to Increased Apoptosis in Trigeminal Ganglia during the Transition from Acute Infection to Latency

Abstract: Bovine herpesvirus 1 (BHV-1) is an important pathogen of cattle and infection is usually initiated via

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 71 publications
5
94
1
Order By: Relevance
“…Consequently, LR-RNA sequences may promote the early phases of establishing latency by binding to bICP0 mRNA sequences, which would inhibit productive infection by reducing bICP0 levels and inducing an earlier IFN response. Our previous studies also indicate that expression of an LR protein promotes survival of infected neurons by inhibiting apoptosis (Ciacci-Zanella et al, 1999;Lovato et al, 2003). In conclusion, we propose that premature expression of LR-RNA by the LR mutant virus, in the absence of LR protein expression, leads to survival of a subset of infected neurons that can establish latency but are unable to reactivate from latency .…”
Section: Virussupporting
confidence: 62%
“…Consequently, LR-RNA sequences may promote the early phases of establishing latency by binding to bICP0 mRNA sequences, which would inhibit productive infection by reducing bICP0 levels and inducing an earlier IFN response. Our previous studies also indicate that expression of an LR protein promotes survival of infected neurons by inhibiting apoptosis (Ciacci-Zanella et al, 1999;Lovato et al, 2003). In conclusion, we propose that premature expression of LR-RNA by the LR mutant virus, in the absence of LR protein expression, leads to survival of a subset of infected neurons that can establish latency but are unable to reactivate from latency .…”
Section: Virussupporting
confidence: 62%
“…Similar to our original studies with HSV-1 (Perng et al, 2000a), a BHV-1 LR mutant containing three stop codons inserted just downstream of the start of open reading frame 2 (ORF2) (the first ORF in LR; see Fig. 1C) has higher levels of apoptosis in TG neurons during the transition from acute infection to latency (establishment of latency) compared to wild-type or marker-rescued virus (Lovato et al, 2003). In transient transfection assays, plasmids expressing LR containing these alterations to ORF2 no longer inhibit apoptosis (Inman et al, 2001a).…”
Section: Introductionmentioning
confidence: 53%
“…The LRT mutants were shed at similar rates from the nasal cavity during the primary infection [80,158]. In latently infected neurons, reduced levels of viral DNA were detected [81] but higher levels of apoptosis occurred in trigeminal ganglion at the end of the acute infection [118]. The BoHV-1 LRT mutants were not re-excreted following a reactivation treatment with dexamethasone, which induced reactivation and re-excretion in all calves infected by either wild-type or LRT rescued virus [81].…”
Section: Latency and Reactivationmentioning
confidence: 93%
“…An immediate onset of apoptosis would decrease BoHV-1 replication at the entry site and prevent therefore its spread. It was also demonstrated that caspase 3, a key regulatory protein in the apoptotic pathway, is activated late during productive BoHV-1 infection [35,118]. BICP0 probably participates in this delayed induction of apoptosis by an indirect mechanism that stimulates caspase 3 cleavage [72].…”
Section: Replication At the Mucosal Portal Of Entrymentioning
confidence: 99%